Oxidized LDL Induces Alternative Macrophage Phenotype through Activation of CD36 and PAFR. (25th August 2013) - Rios, Francisco J.; Koga, Marianna M.; Pecenin, Mateus; Ferracini, Matheus; Gidlund, Magnus; Jancar, S.
Abstract : OxLDL is recognized by macrophage scavenger receptors, including CD36; we have recently found that Platelet-Activating Factor Receptor (PAFR) is also involved. Since PAFR in macrophages is associated with suppressor function, we examined the effect of oxLDL on macrophage phenotype. It was found that the presence of oxLDL during macrophage differentiation induced high mRNA levels to IL-10, mannose receptor, PPAR γ and arginase-1 and low levels of IL-12 and iNOS. When human THP-1 macrophages were pre-treated with oxLDL then stimulated with LPS, the production of IL-10 and TGF- β significantly increased, whereas that of IL-6 and IL-8 decreased. In murine TG-elicited macrophages, this protocol significantly reduced NO, iNOS and COX2 expression. Thus, oxLDL induced macrophage differentiation and activation towards the alternatively activated M2-phenotype. In murine macrophages, oxLDL induced TGF- β, arginase-1 and IL-10 mRNA expression, which were significantly reduced by pre-treatment with PAFR antagonists (WEB and CV) or with antibodies to CD36. The mRNA expression of IL-12, RANTES and CXCL2 were not affected. We showed that this profile of macrophage activation is dependent on the engagement of both CD36 and PAFR. We conclude that oxLDL induces alternative macrophage activation by mechanisms involving CD36 and PAFR.